Religious/spiritual coping and level of hope in patients with cancer in chemotherapy - Diogo Timóteo Costa; Darine Marie Rodrigues da Silva; Iago Dillion Lima Cavalcanti; Eduardo Tavares Gomes; Juliana Lúcia de Albuquerque Vasconcelos; Maria Valéria Gorayeb de Carvalho
ABSTRACT Aim: To demonstrate the relationship between religious/spiritual coping and hope in cancer patients undergoing chemotherapy. Method: This is a cross-sectional, descriptive study with a quantitative approach performed in a reference outpatient clinic in Caruaru, PE, between August and October 2017. A total of 82 cancer patients undergoing chemotherapy were included in the study, using the brief religious/spiritual coping scale (RCOPE-Brief) and the Herth Hope Scale (HHS). Results: The sample presented mean positive RCOPE scores (3.03 ± 0.41) and the level of hope was considered high (42.7 points ± 3.67). Patients who had a high RCOPE score were found to have a higher mean of Herth's level of hope (44.12 points). Conclusion: This study becomes relevant to nursing professionals by encouraging care that takes into account the patient's spiritual dimension in order to stimulate positive mechanisms of religious coping and, consequently, raise the levels of hope.